A million miles in a thousand years : what I learned while editing my life - Miller, Donald, 1971- (Nashville, Tenn. : Thomas Nelson, 2009)
Full of beautiful, heart-wrenching, and hilarious stories, "A Million Miles in a Thousand Years" details one man's opportunity to edit his life as if he were a character in a movie, showing how to get a second chance at life the first time around.
Part I: Exposition -- Part II: A character -- Part III: A character who wants something -- Part IV: A character who wants something and overcomes conflict -- Part V: A character who wants something and overcomes conflict to get it.
Keywords: Miller, Donald, -- 1971-; Christian biography -- United States; Autobiography -- Authorship